Heart failure hospitalization with SGLT-2 inhibitors: a systematic review and meta-analysis of randomized controlled and observational studies. Issue 4 (3rd April 2019) - Singh, Awadhesh Kumar; Singh, Ritu
ABSTRACT: Introduction : Heart failure (HF) in type 2 diabetes mellitus (T2DM) poses a significant increase in mortality. Until recently, anti-diabetic drugs have not been shown to reduce hospitalization due to heart failure (hHF). While thiazolidinedione class and saxagliptin has shown a significantly increased risk, sodium-glucose linked co-transporter 2 inhibitors (SGLT-2Is) have demonstrated a significant reduction in the risk of hHF. Areas covered : We systematically searched the database of PubMed, Embase, ClinicalTrials.gov, and International conference presentation up to 25 December 2018 and retrieved all the studies that were conducted for ≥24 weeks and explicitly reported hHF outcome. Subsequently, we conducted the meta-analysis to study the effect of SGLT-2Is on hHF outcome in randomized controlled trials (RCTs), observational studies, and both. Expert opinion : The meta-analysis of RCTs ( N = 34, 322), observational studies ( N = 15, 36, 339), and both ( N = 15, 70, 661) demonstrated a significant decrease in hHF (OR 0.70, 0.64, 0.66, respectively, all p = 0.000) with SGLT-2Is compared to placebo or other anti-diabetes drugs in T2DM. A significant benefit in hHF (OR 0.68, p = 0.000) is also observed in patients with established HF ( N = 3891) in sub-group meta-analysis of RCTs. Ongoing dedicated HF trials will further enlighten the merits of SGLT-2Is in patients with established heart failure (preserved or reduced) with or without T2DM.